Experimental Study on Seepage Properties of Postpeak Fractured Rocks under Cyclic Loading-Unloading Confining Stress and Axial Stress. (2nd January 2021) - Zhang, Xiaobo; Xia, Zuhao; Yao, Chi; Yang, Jianhua; Yang, Mingdong
Abstract : Excavation in rock masses always encounters safety problems from rock fracture seepage in water-rich areas, which needs to be paid much attention, especially for fractured rocks under complicated stress state. For this reason, the permeability of fractured sandstone and granite is experimentally investigated under cyclic loading-unloading confining stress and axial stress. The variation of permeability coefficient and seepage flow with increasing and decreasing the confining stress and axial stress are comprehensively analyzed. Results show that the changing patterns of permeability with loading-unloading cycles of confining stress for both fractured sandstone and granite are similar. The permeability is most sensitive to the initial loading-unloading stages. After several loading-unloading cycles, the confining stress has little effect on permeability. The seepage flow decreases as the confining stress is unloaded to the same level in the loading process, indicating a hysteresis effect on the recovery of seepage capacity. The seepage properties under cyclic loading-unloading the axial stress are quite different from those under the confining stress. The permeability of fractured sandstone is most sensitive to the first cycle of loading-unloading of axial stress. The irrecoverable shear slide between fractures under the axial stress causes dilatancy or contraction, which makes the permeability coefficient to consecutively decrease at the subsequent cycles. The permeability of granite first decreases during the first loading of axial stress, while this trend is disordered at the subsequent stages no matter loading or unloading the axial stress. This is because of the accumulation of breakage fragments between fractures, which further disturbs the seepage flow. These findings may be useful for further understanding the seepage properties of fractured granite and sandstone under complex loading-unloading history.